The importance of firms' strategic resources and capabilities in crisis situations - Krzeminska, Anna Malgorzata (2015)
The general idea of this research is to analyze overall firm performance before and after the global financial crisis of 2008. The main question is: What kind of strategies did companies adopt that led to positive business performance after the crisis? Are there any particular competitive advantages that bring better performance in the case of an economic downturn? This research focuses on competitive advantage gained by resource-based view attributes of a product (quality, durability and prestige) and dynamic capabilities (strategic flexibility in product development and technological innovation ability). The economic crisis setting provides a proper background to analyze the competitive advantage strategies in a dynamic, low-probability environment to determine which are most worth adopting in the business world. I employ an OLS regression analysis in order to measure the business performance of 136 Brazilian firms across four years – 2002, 2005, 2008 and 2012. The findings indicate that even though all of the strategic resources and capabilities positively influence firm performance in expansionary periods, only the superior product characteristics are pertinent in surviving an economic downturn.